2021
DOI: 10.3389/fpsyg.2020.609571
|View full text |Cite
|
Sign up to set email alerts
|

Study of Sexual Satisfaction in Different Typologies of Adherence to the Sexual Double Standard

Abstract: The sexual double standard (SDS) refers to the acceptance of different criteria to assess the same sexual behavior in men and women. To date, the few studies that have addressed the relationship between SDS and sexual satisfaction have obtained inconclusive results. In addition, no study has analyzed sexual satisfaction in people who maintain different forms of adherence to the SDS. This study establishes three SDS typologies of adherence (man-favorable, woman-favorable, egalitarian) in two areas of sexual beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 69 publications
1
11
0
7
Order By: Relevance
“…The number of sexual partners also had a significant effect on the subjective experience of orgasm in comparisons by sex in the gay group and by sexual orientation, in men. Generally, it is men who tend to report a higher number of sexual partners, both in gay [ 30 , 66 ] and heterosexual [ 66 , 79 ] populations—a fact that could respond to the phenomenon of sexual double standard (see Álvarez-Muelas et al [ 36 , 80 ] and Endendijk et al [ 81 ]). Finally, the method used to obtain the last orgasm in sexual relationships with another person turned out to be a significant variable in the comparison by sex within the group of gay people, and by sexual orientation, in men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of sexual partners also had a significant effect on the subjective experience of orgasm in comparisons by sex in the gay group and by sexual orientation, in men. Generally, it is men who tend to report a higher number of sexual partners, both in gay [ 30 , 66 ] and heterosexual [ 66 , 79 ] populations—a fact that could respond to the phenomenon of sexual double standard (see Álvarez-Muelas et al [ 36 , 80 ] and Endendijk et al [ 81 ]). Finally, the method used to obtain the last orgasm in sexual relationships with another person turned out to be a significant variable in the comparison by sex within the group of gay people, and by sexual orientation, in men.…”
Section: Discussionmentioning
confidence: 99%
“…Participation was voluntary and anonymous. Online questionnaires were used, which is a procedure equally valid as the traditional paper-and-pencil procedure in studies of this type [ 36 , 37 ]. Using the Open-Source LimeSurvey platform, located on the servers of the University of Granada, an electronic version of the survey was disseminated through Facebook ® .…”
Section: Methodsmentioning
confidence: 99%
“…For example, interventions in negative attitudes toward masturbation are included in sexual education programs to improve different sexual health aspects [ 62 , 63 ]. Therefore, sexual education can promote positive sexual attitudes to do away with, for example, gender roles [ 45 , 64 ] or discrimination against sexual minorities [ 65 , 66 ] which limit sexual health. Therefore, these findings can help effective therapies and programs to be developed that promote, in particular, sexual wellbeing and quality of life in general.…”
Section: Discussionmentioning
confidence: 99%
“…This method was normally used in research works about sexual behaviors. There were no differences between the data obtained by this system and those acquired by the traditional paper and pencil methods [ 45 , 46 ]. The IP address was controlled, as were automatic responses to avoid automated responses.…”
Section: Methodsmentioning
confidence: 99%
“…(2021b) proposed different typologies of adherence to the SDS, namely egalitarian, man-favorable and woman-favorable. By doing so, these authors observed that those men who defend a gender egalitarian stance for sexual freedom feel more sexually satisfied than those men with a man-favorable typology ( Álvarez-Muelas et al., 2021a ).…”
mentioning
confidence: 97%